The AaFoxA factor regulates female reproduction through chromatin remodeling in the mosquito vector Aedes aegypti - Yang Cheng; Xuesong Wang; Yike Ding; Houhong Zhang; Zhenyu Jia; Alexander S. Raikhel (Proceedings of the National Academy of Sciences, 2025)
Female mosquitoes are vectors of many devastating human diseases because they require blood feeding to initiate reproduction. Thus, elucidation of molecular mechanisms managing female mosquito reproduction is essential. Although the regulation of gene expression during the mosquito gonadotrophic cycle has been studied in detail, how this process is controlled at the chromatin level remains unclear. Chromatin must be accessible for transcription factors (TFs) governing gene expression. A specialized class of TFs, called pioneer factors (PFs), binds and remodels closed chromatin, permitting other TFs to bind DNA and activate the gene expression. Here, we identified a homolog of the vertebrate PF FoxA in the mosquito Aedes aegypti and used the CRISPR-Cas9 system to generate mosquitoes deficient in AaFoxA . We found that ovary development was severely retarded in mutant females. Multiomics and molecular biology analyses have shown that AaFoxA increased histone acetylation and decreased methylation of H3K27 by controlling the chromatin accessibility of histone modification enzymes and chromatin remodelers. AaFoxA is bound to the loci of chromatin remodelers, changing their chromatin accessibility and modulating their temporal expression patterns. AaFoxA increased the accessibility of the ecdysone receptor (EcR) and E74 loci, indicating the important role of AaFoxA in the hormonal regulation of mosquito reproductive events. Further, the CUT&RUN and ATAC-seq analyses revealed that AaFoxA temporarily bound closed chromatin, making it differentially accessible during the mosquito gonadotrophic cycle. Hence, this study demonstrates that AaFoxA modulates chromatin dynamics throughout female mosquito reproduction.